2015
DOI: 10.3126/jbs.v1i2.11863
|View full text |Cite
|
Sign up to set email alerts
|

Place of delivery and newborn care practices in Kaski district: a cross sectional study from Nepal

Abstract: Background: First 28 days of life is known as neonatal period. Newborn care is important for the proper development and healthy life of a baby. During these days they have more risk of mortality, so special care, support and appropriate feeding is needed for healthier life. The main objective of study was to assess the place of delivery and newborn care practices in Pumdi Bhumdi VDC, Kaski, Nepal. Methods: A descriptive, cross-sectional study was carried out among 245 mothers having children aged upto 2 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…A study done in Uganda among (10-19 years) adolescents' girls in 2018 found that 18.9% were stunting [19]. A study done in India in 2013 among orphan and non-orphan children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years founds that 37.1% were stunting [1], which is quite similar to our study ndings. The high rate of stunting was not surprising as the children's home participants are more likely to have grown up in poor condition.…”
Section: Declarationssupporting
confidence: 89%
See 3 more Smart Citations
“…A study done in Uganda among (10-19 years) adolescents' girls in 2018 found that 18.9% were stunting [19]. A study done in India in 2013 among orphan and non-orphan children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years founds that 37.1% were stunting [1], which is quite similar to our study ndings. The high rate of stunting was not surprising as the children's home participants are more likely to have grown up in poor condition.…”
Section: Declarationssupporting
confidence: 89%
“…A study done in Bangladesh in 2013 among (5-14 year) orphan children founds that 65% children were underweight which were similar to our ndings [17]. A study done among orphan children (6)(7)(8)(9)(10)(11)(12)(13)(14) year in 2018 in India founds that 55.7% were underweight [13]. Also, another study from India done in 2013 among orphan and non-orphan children (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) years founds that 45.7% were underweight [1].…”
Section: Declarationssupporting
confidence: 83%
See 2 more Smart Citations
“…A study done in Bangladesh in 2013 among (5-14 year) orphan children founds that 65% children were underweight which were similar to our ndings [17]. A study done among orphan children (6)(7)(8)(9)(10)(11)(12)(13)(14) year in 2018 in India founds that 55.7% were underweight [13]. Also, another study from India done in 2013 among orphan and non-orphan children (6-16) years founds that 45.7% were underweight [1].…”
Section: Declarationssupporting
confidence: 83%